Healthcare Resource Use and Cost: The Impact of Adopting an Abuse-Deterrent Formulation of Extended Release Morphine - Rossiter LF; Kwong WJ; Marrett E (ClinicoEconomics and Outcomes Research, 2020)
Louis F Rossiter, 1 Winghan Jacqueline Kwong, 2 Elizabeth Marrett 2 1The College of William and Mary, Williamsburg, VA 23187, USA; 2US Medical Affairs, Daiichi Sankyo, Inc., Basking Ridge, NJ 07920, USACorrespondence: Elizabeth MarrettUS Medical Affairs Daiichi Sankyo, Inc., 211 Mt. Airy Road, Basking Ridge, NJ 07920, USATel +908 992 7050Email emarrett@dsi.comBackground: Development of abuse-deterrent formulations (ADFs) of prescription opioids (RxO) is an important step toward reducing misuse and abuse. Morphine-ARER (MorphaBond™ ER) is an extended-release (ER) morphine sulfate tablet formulated to deter misuse/abuse via intravenous (IV) and intranasal (IN) routes of administration.Objective: A model was developed to estimate the budget impact to a hypothetical commercial health plan of 10 million members 2 years after adding morphine-ARER to drug formulary.Methods: We analyzed incremental health care resource use (HCRU) associated with RxO misuse/abuse based on a health plan’s RxO formulary coverage and patterns of misuse/abuse. Misuse/abuse rates, incremental HCRU and associated costs were based on the 2015 National Survey on Drug Use and Health, an analysis of claims from OptumHealth Care Solutions, Inc. (2013– 2015) and published literature. RxO formulary shares were based on 2016– 2017 Symphony Retail Prescription data. Morphine-ARER was assumed to capture 20 and 30 percent from branded and 0.3 and 0.6 percent from generic non-ADF ER morphine, in the first and second years, respectively. Proportions of misuse/abuse deterred by physical/chemical properties of morphine-ARER were assumed to be 90 percent via IV and 60 percent via IN administration, with further IN deterrence based on results from morphine-ARER’s human abuse liability study.Results: Adding morphine-ARER to formulary resulted in a potential decrease in abuserelated healthcare costs by $557,321 (−$0.00232 per-member per-month [PMPM]), offsetting a pharmacy cost increase of $217,045 (+$0.00090 PMPM), resulting in net cost-savings of $0.00142 PMPM over 2 years, based on certain model assumptions. Conclusion: Placing morphine-ARER on a health plan’s drug formulary may result in reduced misuse/abuse and overall cost savings. Keywords: prescription opioids, abuse-deterrent formulations, drug formulary change, budget impact